2018
DOI: 10.1016/j.foodres.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the health benefits of consumption of extruded tannin sorghum with unfermented probiotic milk in individuals with chronic kidney disease

Abstract: This study investigated the chemical and nutritional composition of breakfast cereal based on whole sorghum, and the effect of its association with unfermented probiotic milk on the inflammation and oxidative stress of individuals with chronic kidney disease. Extruded sorghum breakfast meal presented higher carbohydrate concentration (approximately 71%), followed by protein (approximately 11%) and lipid (approximately 0.4%). When compared to extruded maize breakfast meal, it presented higher percentage of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 48 publications
(41 reference statements)
1
28
0
Order By: Relevance
“…In contrast, cereals of nontannin white sorghum had comparable nutritional compositions and sensory acceptance to a successful commercial oat cereal (Mkandawire et al., ). In addition, the combination of sorghum RTE cereals with unfermented probiotic milk has been shown to reduce oxidative stress and inflammation in people with chronic kidney diseases (Lopes et al., ). Consumption of sorghum‐based foods can promote human health, and tannin sorghum could be the most beneficial food ingredient, although the sensory quality should be further improved.…”
Section: Application Of Sorghum Grain In the Food Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cereals of nontannin white sorghum had comparable nutritional compositions and sensory acceptance to a successful commercial oat cereal (Mkandawire et al., ). In addition, the combination of sorghum RTE cereals with unfermented probiotic milk has been shown to reduce oxidative stress and inflammation in people with chronic kidney diseases (Lopes et al., ). Consumption of sorghum‐based foods can promote human health, and tannin sorghum could be the most beneficial food ingredient, although the sensory quality should be further improved.…”
Section: Application Of Sorghum Grain In the Food Systemmentioning
confidence: 99%
“…Sorghum may be an attractive option for use in extruded RTE cereals. Studies have shown that the RTE breakfast cereals made of sorghum whole grain, especially the tannin sorghum, were a rich source of dietary fiber and phenolic compounds with high antioxidant activity (Anunciacao et al, 2017;Lopes et al, 2018;Mkandawire, Weier, Weller, Jackson, & Rose, 2015). The cereals made of tannin sorghum, besides the high nutritional values and health potential, had higher sensory acceptance than wheat cereals (Anunciacao et al, 2017).…”
Section: Sorghum Grain As Functional Foods and Beveragesmentioning
confidence: 99%
“…As the number of obese individuals and their associated diseases continues to increase, nutritional strategies aiming to prevent and treat obesity have been the focus of many studies (Belobrajdic et al, 2011;Goto et al, 2011). Sorghum (Sorghum bicolor L.), a cereal native to Africa and a member of the Poaceae family, may have nutritional and functional value of potential benefit to human health (Lopes et al, 2018;Stefoska-Needham et al, 2015). Among the sorghum genotypes, grains with the pericarp and pigmented forehead have a high content of phenolic acids, 3-deoxyanthocyanidins (3-DXA), and proanthocyanidins (tannins) (Cardoso et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the sorghum genotypes, grains with the pericarp and pigmented forehead have a high content of phenolic acids, 3-deoxyanthocyanidins (3-DXA), and proanthocyanidins (tannins) (Cardoso et al, 2015). These compounds are effective in the modulation of diseases such as cancer, obesity, diabetes, cardiovascular diseases, and others (Cardoso et al, 2017;Lopes et al, 2018). Chung et al (2011) reported that oral ingestion of extracts of sorghum phenolic compounds (100 to 250 mg/kg for 14 days) is effective in reducing plasma cholesterol concentration and triacylglycerol in rats, and recent studies by our research group found that extruded sorghum flour can effectively reduce lipogenesis by reduced fatty acid synthase gene expression, improve sensitivity to insulin and reduce inflammatory cytokines, including tumor necrosis factor alpha (Arbex et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these cereals, sorghum has stood out because its higher phytochemical content compared to wheat (Anunciação et al, 2017), one of the major cereals produced and consumed in Brazil. Our group has previously conducted sorghum (Sorghum bicolor L.) characterization studies (Anunciação et al, 2017;Cardoso et al, 2015a;Cardoso et al, 2015b;Lopes et al, 2018) and verified that sorghum, especially the SC319 genotype, stands out as an excellent source of bioactive compounds including flavonoids, tannins, anthocyanins, vitamin E and carotenoids, which contribute to its high antioxidant capacity. Whole-grain wheat breakfast cereal is also a good source of vitamin E and phenolic compounds, contributing to its antioxidant capacity (Anunciação et al, 2017).…”
Section: Introductionmentioning
confidence: 96%